Importance of delayed reperfusions in patients with incomplete thrombectomy - Mujanović, Adnan; Jungi, Noel; Kurmann, Christoph C.; Dobrocky, Tomas; Meinel, Thomas Raphael; Almiri, William; Grunder, Lorenz; Beyeler, Morin; Lang, Matthias F.; Jung, Simon; Klail, Tomas; Hoffmann, Angelika; et al. (Stroke, 2022)
Background: - - There is paucity of data regarding the effects of delayed reperfusion (DR) on clinical outcomes in patients with incomplete reperfusion following mechanical thrombectomy. We hypothesized that DR has a strong association with clinical outcome in patients with incomplete reperfusion after mechanical thrombectomy (expanded Thrombolysis in Cerebral Infarction, 2a-2c). - - Methods: - - Single-institution’s stroke registry retrospective analysis of patients admitted from February 2015 to December 2020. DR was defined as the absence of any perfusion delay on ≈24-hour contrast-enhanced follow-up perfusion imaging, whereas persistent perfusion deficit denotes a perfusion delay corresponding to the catheter angiographic deficit directly after the intervention. The association of perfusion outcome (DR versus persistent perfusion deficit) with the occurrence of new infarcts and 90-day functional independence (modified Rankin Scale score 0-2) was evaluated using logistic regression analyses. Comparison of predictive accuracy was evaluated by calculating area under the curve for models with and without perfusion outcome. - - Results: - - In 566 patients (mean age 74, 49.6% female), new infarcts in the incomplete reperfusion areas were less common in DR versus persistent perfusion deficit patients (small punctiform: 17.1% versus 25%, large confluent: 7.9% versus 63.2%; P=0.001). After adjustment for confounders, DR was a strong predictor of functional independence (adjusted odds ratio, 2.37 [95% CI 1.34-4.23]). There was a significant improvement in predictive accuracy of functional independence when perfusion outcome was added to expanded Thrombolysis in Cerebral Infarction alone (area under the curve 0.57 versus 0.62, P=0.01). - - Conclusions: - - Occurrence of DR is closely associated with tissue outcome and functional independence. DR may be an independent prognostic parameter, suggesting it as a potential outcome surrogate for medical rescue therapies.
Gesehen am 17.01.2023